Stinging Trichome Density and Morphology of Three Nettle Species Reflect Mountain Gorillas' Feeding Behavior - Alphonse Nyandwi; Winnie Eckardt; Elias Bizuru; Myriam Mujawamariya; Melanie L. DeVore (Ecology and Evolution, 2025)
ABSTRACT Plants have developed defense mechanisms against herbivory, including stinging trichomes. Unlike smaller trichomes, which deter insects, the larger, biomineralized, stinging trichomes in Urticaceae defend plants from mammals. The trichome tip breaks off, pierces the skin, and injects irritants, causing an immediate sensation of pain. The herbivore will cease consuming the plant. Some herbivores process and consume nettles. Volcanoes National Park (VNP) in Rwanda provides habitat for several large folivores, including the endangered mountain gorilla (Gorilla beringei beringei). VNP mountain gorillas feed on stinging nettle species, including Laportea alatipes, Urtica massaica, and Girardinia bullosa. We investigated the link between the importance (proportion) of these stinging nettles in the diet of gorilla groups ranging in the southwest of VNP and their level of defense through assessing trichome density, length, and glandular base length from each plant organ of 15 specimens per nettle species, which were photographed with a scale ruler under a digital microscope. We also videotaped 12 mountain gorillas consuming L. alatipes to examine adapted feeding techniques to cope with stinging trichomes. We found that L. alatipes, which is consumed most frequently of the three study nettles, had a significantly higher stinging trichome density compared to U. massaica and G. bullosa. However, the length of stinging trichomes and glandular bases containing irritating secretions were significantly smaller in L. alatipes and U. massaica than in G. bullosa, from which gorillas almost exclusively avoid consuming aboveground organs covered with long trichomes. This suggests that larger stinging trichomes and secretory glandular bases offer a more effective defense against mountain gorillas than increased trichome density. The trichome density of L. alatipes tended to be higher on top leaves and stem sections, which are consumed by gorillas more frequently compared to lower parts. Plants have evolved in an intricate way to adapt to herbivores' attacks.